Unit Cost Analysis of Sectio Caesarea with Activity-Based Costing in Yogyakarta City Hospital - Rijal Maulana Haqim; Firman Pribadi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
The selection of unit cost calculation method in hospital services is a challenge for hospitals. Errors in the selection of the calculation method will make a big difference in the final results of the total costs required after the service. Yogyakarta City Hospital still uses traditional methods of determining service rates. Design of this study is a qualitative study with a case study approach to the unit costs required for uncomplicated section Caesarea which is calculated using the activity-based costing method compared to the unit cost of section Caesarea calculated using traditional methods. The purposes are to know the differences between the two methods. The results of this study indicate the unit cost of uncomplicated section Caesarea using the ABC method is IDR 2,703,919. the action rate by the hospital is IDR. 3,051,000, greater than the ABC method. The difference obtained is Rp 347,081. The Conclusions is a positive difference between the unit cost of the ABC method and the hospital rate so it is necessary to evaluate the service rates in Yogyakarta City Hospital.